Towards an understanding of configurational and national influences on international integration in the HR function in MNCs. Issue 7 (17th March 2022) - Edwards, Tony; Tregaskis, Olga; McDonnell, Anthony
Abstract: The human resource (HR) function plays a critical role in how multinational companies (MNCs) centralise decision-making or coordinate and exploit expertise internationally. However, there has been limited attention on the extent to which the HR function in MNCs is integrated internationally and the influencing factors behind this. Using nationally representative, cross-country comparative data, this paper identifies the degree to which internationally integrated HR functions exist and test the extent to which this is shaped by the strategy, structure and nationality of the MNC. We demonstrate the multidimensionality of an internationally integrated HR function; with the structural configuration, level of inter-dependencies between MNC operations and country of origin each partially impacting its nature. A key implication concerns the need to move beyond solely focusing on either nationality as per institutionalist theory, or corporate strategy and structure as characterised in the strategic international HRM literature, towards an integrated explanation that incorporates both sets of factors.